Advances in neuroimaging in cancer-related cognitive impairment - Li, Jinxin; Cui, Feiyun; Yang, Yuanshan; Zhang, Qingting; Zeng, Lijiao; Li, Yulun; Zhang, Yunxian; Huang, Jinbai; Wang, Wei (Frontiers in Human Neuroscience, 2026)
Cancer-related cognitive impairment (CRCI) is a cognitive dysfunction of the brain caused by the tumor itself and antitumor treatments such as radiotherapy, chemotherapy, endocrine therapy, and surgery. As a common complication of cancer, CRCI significantly affects patients’ quality of life. In recent years, the neurobiological mechanisms of CRCI have garnered widespread attention. Research indicates that cancer-related therapies lead to CRCI by affecting brain structure, function, metabolism, and blood perfusion. Various neuroimaging techniques, including magnetic resonance imaging (MRI), positron emission tomography (PET), and electroencephalography (EEG), have been extensively employed to investigate the neurobiological underpinnings of CRCI. This article reviews recent advancements in neuroimaging research on CRCI, focusing on its influencing factors and the neural mechanisms underlying different cognitive domains, and summarizes findings from relevant animal model studies.